2018
DOI: 10.1016/j.amsu.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Roux-en-Y gastric bypass is as safe as laparoscopic sleeve gastrectomy. Results of a comparative cohort study

Abstract: BackgroundA meta-analysis and six randomized controlled trials show higher 30-day complication rates with laparoscopic Roux-en-Y gastric bypass (LRYGB) than with laparoscopic sleeve gastrectomy (LSG).AimTo identify any difference in 30-day outcomes of patients treated with LRYGB or LSG when a standardized technique and identical post-operative protocol was followed with all procedures being conducted either by or under the supervision of a single consultant surgeon who had significant experience in bariatric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Individually, the rates of specific complications compared favorably with NSQIP and the Michigan Bariatric Surgical Collaborative with similar rates of acute renal failure (0.1% vs. 0.1% and 0.2% respectively), urinary tract infection (0.5% vs. 0.7% and 0.3% respectively), pneumonia (0.2% vs. 0.5% and 0.9% respectively), unplanned intubation (0.2% vs. 0.3% and 0.4% respectively), vein thrombosis (0.1% vs. 0.3% and 0.4% respectively), and death (0.1% vs. 0.2% and 0.1% respectively). Overall, the higher complication rate in this study appears to be driven by the increased number of complications recorded in the 2016 [10]. And although a large meta-analysis of singlecenter studies did not find any difference in leak or mortality rates between LRYGB and LSG, most reported data shows an increased complication rate in patients undergoing LRYGB versus LSG [11][12][13].…”
Section: Discussionmentioning
confidence: 46%
“…Individually, the rates of specific complications compared favorably with NSQIP and the Michigan Bariatric Surgical Collaborative with similar rates of acute renal failure (0.1% vs. 0.1% and 0.2% respectively), urinary tract infection (0.5% vs. 0.7% and 0.3% respectively), pneumonia (0.2% vs. 0.5% and 0.9% respectively), unplanned intubation (0.2% vs. 0.3% and 0.4% respectively), vein thrombosis (0.1% vs. 0.3% and 0.4% respectively), and death (0.1% vs. 0.2% and 0.1% respectively). Overall, the higher complication rate in this study appears to be driven by the increased number of complications recorded in the 2016 [10]. And although a large meta-analysis of singlecenter studies did not find any difference in leak or mortality rates between LRYGB and LSG, most reported data shows an increased complication rate in patients undergoing LRYGB versus LSG [11][12][13].…”
Section: Discussionmentioning
confidence: 46%
“…However, there is a sharp trend towards the utilization of LSG over the last decade and a decline in the use of LRYGB [8,9]. Some studies suggest that LSG is easier and faster to perform and potentially safer compared with LRYGB [8,10], while some indicate that LRYGB is more potent than LSG [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The safety and efficacy of LSG versus LRYGB are controversial. Severe studies suggested that LSG is an easier surgery with lower complication rate and shorter learning curve than LRYGB; however, some studies demonstrated that LRYGB is as safe as LSG . The outcomes of meta‐analyses comparing LSG and LRYGB are discrepant.…”
Section: Introductionmentioning
confidence: 99%